Pemanfaatan Instagram Membangun Brand Awereness Cinemora Pictures - Muhammad Adri Ghafar; Satya Indra (Bandung Conference Series: Communication Management, 2022)
Abstract. The local film industry in Indonesia is currently in a good trend, one of the production houses that is currently on the rise and has quality film works in Bandung is a production house called Cinemora Picture's. Successfully getting awards through works displayed at national and international short film festivals, Cinemora Picture's in 2021 made a breakthrough by making events that are held regularly. An event activity requires careful planning so that the message management and marketing techniques used can attract the interest of the audience to come to the event organized by the organizer. The theory used in this research is the theory of Communication Strategy from Cangara Hafied. The collection technique will be done by means of observation, interviews and documentation. Abstrak. Industri film lokal di Indonesia saat ini sedang dalam trend yang baik, salah satu rumah produksi yang saat ini sedang meningkat dan memiliki karya film yang berkualitas di Bandung adalah rumah produksi bernama Cinemora Picture’s. Berhasil mendapatkan pengghargaan melalui karya-karya yang ditampilkan pada festival film pendek nasional maupun internasional, Cinemora Picture’s ditahun 2021 satu ini membuat sebuah terobosan dengan membuat kegiatan Event yang diselenggarakan secara berkala. Sebuah kegiatan event membutuhkan perencaanaan yang matang agar penggelolaan pesan dan teknik pemasaran yang digunakan dapat menarik minat penonton untuk datang pada acara yang diselenggarakan oleh penyelenggara. Teori yang digunakan dalam penelitian ini adalah teori Strategi Komunikasi dari Cangara Hafied. Teknik pengumpulan akan dilakukan dengan cara observasi, wawancara dan dokumentasi.